The Influence of Work Family Conflict and Work Life Balance on Employee Performance at PT. Samudera Pastry Indonesia - Chamelia, Stevany; Joesyiana, Kiki; Susanti, Desi (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2023)
This research aims to determine the effect of work family conflict and work life balance on employee performance at PT Samudera Pastry Indonesia which is based on the fact that many employees are not yet optimal in carrying out their performance with clear evidence that many people still make mistakes, paying little attention to product quality, not being on time and targeting not achieved and also a lack of independence in completing tasks. With this, researchers conducted research with the aim of finding ways to improve the quality of employee performance. The population in this research is all employees who work at PT Samudera Pastry Indonesia, totaling 39 people. Data collection techniques in this research were interviews and questionnaires with data analysis using descriptive methods and using multiple regression. The conclusion obtained from the research results is that work family conflict and work life balance have a significant effect on the performance of PT Samudra Pastry Indonesia employees with a contribution of 81.6%, while the remaining 18.4% is determined by other factors not observed in this research.